Suppression of the growth of human colorectal cancer cells by therapeutic stem cells expressing cytosine deaminase and interferon‐β via their tumor‐tropic effect in cellular and xenograft mouse models. Issue 3 (19th January 2013) - Yi, Bo-Rim; Park, Min-Ah; Lee, Hye-Rim; Kang, Nam-Hee; Choi, Kelvin J.; Kim, Seung U.; Choi, Kyung-Chul
Abstract : Genetically engineered stem cells (GESTECs) exhibit a potent therapeutic efficacy via their strong tumor tropism toward cancer cells. In this study, we introduced the human parental neural stem cells, HB1.F3, with the human interferon beta (IFN‐β) gene which is a typical cytokine gene that has an antitumor effect and the cytosine deaminase (CD) gene from Escherichia coli (E. coli) that could convert the non‐toxic prodrug, 5‐fluorocytosine (5‐FC), to a toxic metabolite, 5‐fluorouracil (5‐FU). Two types of stem cells expressing the CD gene (HB1.F3.CD cells) and both the CD and human IFN‐β genes (HB1.F3.CD.IFN‐β) were generated. The present study was performed to examine the migratory and therapeutic effects of these GESTECs against the colorectal cancer cell line, HT‐29. When co‐cultured with colorectal cancer cells in the presence of 5‐FC, HB1.F3.CD and HB1.F3.CD.IFN‐β cells exhibited the cytotoxicity on HT‐29 cells via the bystander effect. In particular, HB1.F3.CD.IFN‐β cells showed the synergistic cytotoxic activity of 5‐FU and IFN‐β. We also confirmed the migration ability of HB1.F3.CD and HB1.F3.CD.IFN‐β cells toward HT‐29 cells by a modified migration assay in vitro, where chemoattractant factors secreted by HT‐29 cells attracted the GESTECs. In a xenograft mouse model, the volume of tumor mass was decreased up to 56% in HB1.F3.CD injected mice while the tumor mass was greatly inhibited about 76% in HB1.F3.CD.IFN‐β injected mice. The therapeutic treatment by these GESTECs is a novel strategy where the combination of the migration capacity of stem cells as a vector for therapeutic genes towards colorectal cancer and a synergistic antitumor effect of CD and IFN‐β genes can selectively target this type of cancer. Highlights: ► Migratory effect of the stem cells was confirmed towards HT‐29 colorectal cancer. ► Therapeutic effect of the stem cells was observed against HT‐29 colorectal cancer. ► The volume of colorectal tumor mass was inhibited in xenografted mice. ►  A remarkable synergistic antitumor effect of CD and IFN‐b genes can selectively target this type of cancer.